2005
DOI: 10.1001/archinte.165.1.55
|View full text |Cite|
|
Sign up to set email alerts
|

The Obesity Paradox

Abstract: In a cohort of outpatients with established HF, higher BMIs were associated with lower mortality risks; overweight and obese patients had lower risk of death compared with those at a healthy weight. Understanding the mechanisms and impact of the "obesity paradox" in patients with HF is necessary before recommendations are made concerning weight and weight control in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
122
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(134 citation statements)
references
References 41 publications
11
122
1
Order By: Relevance
“…Elevated levels of cholesterol have been reported to be a good predictor of survival in other populations including chronic heart failure [20], chronic respiratory failure [21], HIV [22], cancer [22] and rheumatoid arthritis [23]. Liu et al [12] reported a higher death rate from CVD in patients with low cholesterol levels, yet this relationship was not reported when patients had normal levels of inflammation and did not experience malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of cholesterol have been reported to be a good predictor of survival in other populations including chronic heart failure [20], chronic respiratory failure [21], HIV [22], cancer [22] and rheumatoid arthritis [23]. Liu et al [12] reported a higher death rate from CVD in patients with low cholesterol levels, yet this relationship was not reported when patients had normal levels of inflammation and did not experience malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Increased BMI is associated with an increased risk of heart failure. However, in contrast to what is observed in the general population, Curtis et al 27 found out that overweight patients with heart failure have a lower risk of death, when compared to patients who have a healthy weight. These findings confirm the existence of an "obesity paradox" among patients with established heart failure 27 .…”
mentioning
confidence: 81%
“…However, in contrast to what is observed in the general population, Curtis et al 27 found out that overweight patients with heart failure have a lower risk of death, when compared to patients who have a healthy weight. These findings confirm the existence of an "obesity paradox" among patients with established heart failure 27 . However, if obesity is protective, then loss of weight attempts could be associated with increased mortality risk 26 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…BMI and total body fat were also independently predictive of event‐free survival 39. The existence of obesity paradox in chronic stable HF has been described extensively in the literature 5, 38, 40, 41…”
Section: Obesity Paradox In Chronic Stable and Acute Decompensated Hementioning
confidence: 93%